Non contiguous-finished genome sequence and description of Clostridium jeddahense sp. nov. Issue 3 (November 2014) - Lagier, Jean-Christophe; Bibi, Fehmida; Ramasamy, Dhamodharan; Azhar, Esam; Robert, Catherine; Yasir, Muhammad; Jiman-Fatani, Asif; Alshali, Khalid; Fournier, Pierre-Edouard; Raoult, Didier
Abstract Clostridium jeddahense strain JCDT (= CSUR P693 = DSM 27834) is the type strain ofC. jeddahense sp. nov. This strain, whose genome is described here, was isolated from the fecal flora of an obese 24 year-old Saudian male (BMI=52 kg/m2 ).Clostridium jeddahense strain JCDT is an obligate Gram-positive bacillus. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 3, 613, 503 bp long genome (1 chromosome, no plasmid) exhibits a G+C content of 51.95% and contains 3, 462 protein-coding and 53 RNA genes, including 4 rRNA genes.